The effects of elevated CO2 concentration on competitive interaction between aceticlastic and syntrophic methanogenesis in a model microbial consortium - Kato, Souichiro; Yoshida, Rina; Yamaguchi, Takashi; Sato, Tomoyuki; Yumoto, Isao; Kamagata, Yoichi (Frontiers in Microbiology, 2014)
Investigation of microbial interspecies interactions is essential for elucidating the function and stability of microbial ecosystems. However, community-based analyses including molecular-fingerprinting methods have limitations for precise understanding of interspecies interactions. Construction of model microbial consortia consisting of defined-mixed cultures of isolated microorganisms is an excellent method for research on interspecies interactions. In this study, a model microbial consortium consisting of microorganisms that convert acetate into methane directly (Methanosaeta thermophila) and syntrophically (Thermoacetogenium phaeum and Methanothermobacter thermautotrophicus) was constructed and the effects of elevated CO2 concentrations on intermicrobial competition were investigated. Analyses on the community dynamics by quantitative RT-PCR and fluorescent in situ hybridization targeting their 16S rRNAs revealed that high concentrations of CO2 have suppressive effects on the syntrophic microorganisms, but not on the aceticlastic methanogen. The pathways were further characterized by determining the Gibbs free energy changes (ΔG) of the metabolic reactions conducted by each microorganism under different CO2 concentrations. The ΔG value of the acetate oxidation reaction (T. phaeum) under high CO2 conditions became significantly higher than -20 kJ per mol of acetate, which is the borderline level for sustaining microbial growth. These results suggest that high concentrations of CO2 undermine energy acquisition of T. phaeum, resulting in dominance of the aceticlastic methanogen. This study demonstrates that investigation on model microbial consortia is useful for untangling microbial interspecies interactions, including competition among microorganisms occupying the same trophic niche in complex microbial ecosystems.